THE EFFECT OF FIXED ASSETS, TOTAL INCOME, AND TOTAL DEBT ON NET INCOME IN PT. GARUDA INDONESIA (PERSERO) PERIOD 2014 – 2020 - Neneng Susanti; Alya Nabila; Ekky Nurjaman; Abiyan Akbar (Jurnal Manajemen Industri dan Logistik, 2021)
The purpose of conducting this research is to determine the financial performance of PT Garuda Indonesia in the period 2014-2020 which is reviewed through report posts finance is an asset fixed , total income and total debt as the independent variable and net income as the dependent variable. The data used are secondary data in the form of financial reports and annual reports obtained from the official website of PT Garuda Indonesia. Which method used in this study is a descriptive and verification combination method with quantitative approach to conclude data in the form of numbers into descriptive analysis. The technique taken is a saturated sampling technique. By using eviews 12, the results show that partially total income has a significant effect on net income, but assets still has no significant effect on net income, the same as total debt has no significant effect on net profit. But simultaneously assets Fixed income, total income, total debt have an effect on net income.